KUALITAS KUE SEMPRONG SUBSTITUSI TEPUNG MOCAF DENGAN PENAMBAHAN KULIT JERUK PURUT - Salwina Maharani Suryanto; Rusilanti; Cucu Cahyana (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
This study aims to analyze the quality of semprong cake substituted with mocaf flour with the addition of kaffir lime peel. This study uses an experimental method to produce the best formula. The study was conducted at the Pastry and Bakery Laboratory of the Applied Undergraduate Study Program of Culinary Arts and Food Service Management, Faculty of Engineering, Jakarta State University. The aspects analyzed were shape, color, aroma of mocaf flour, aroma of kaffir lime, sweetness, taste of mocaf flour, aspect of kaffir lime flavor, and aspect of crispiness. Validation tests were carried out by 10 trained panelists consisting of 5 expert lecturers and 5 experts from the industry. The results of the study showed that semprong cake substituted with 70% mocaf flour had the highest average value and a rather symmetrical shape (3.7), brownish yellow color (4.3), slightly aromatic with mocaf flour (3.7), slightly aromatic with kaffir lime (3.5), slightly sweet taste (3.7), no mocaf flour taste (4.1), slightly aromatic with kaffir lime (3.9), and crispy (4.2). In semprong cake, 80% mocaf flour substitution produces a symmetrical shape (4.1), brownish yellow (4), slightly mocaf flour aroma (3.2), slightly kaffir lime aroma (3.6), slightly sweet (3.4), slightly mocaf flour taste (3.8), slightly kaffir lime taste (3.9), and crispy (4.1) and in semprong cake, 90% mocaf flour substitution produces a slightly symmetrical shape (3.9), brownish yellow (4.1), slightly mocaf flour aroma (3), slightly kaffir lime aroma (3), slightly sweet (3.6), slightly mocaf flour taste (3), slightly kaffir lime taste (3.3), and crispy (4.3). With these results, semprong cake with 70%, 80%, and 90% mocaf flour substitution with the addition of kaffir lime peel is declared worthy to undergo consumer acceptance test